Analysis of The Influence Between Job Stress, Workload and Job Satisfaction (Literature Review) - Wulandari, Dewi Sri; Khaerudin, Khaerudin (Dinasti International Journal of Management Science, 2025)
Developments in the era of modern technology, especially the science of information technology is growing rapidly. This challenges employees to be able to quickly adapt to technological changes and affect the speed of providing services to customers. Problems commonly encountered in the world of work, especially in maintaining the quality and quality of Service is the speed and accuracy of providing excellent service to customers. This creates a high level of stress and workload that can negatively affect employee job satisfaction. This is because employees will always try to maintain performance by providing the best service to customers but on the other hand there are sales targets that become workloads resulting in work stress which affects employees who are dissatisfied with their work so they tend to show a negative attitude towards their duties and experience higher levels of stress during the job. The purpose of the study to analyze the relationship between workload and job stress on employee job satisfaction. This study uses the approach of the method used in this study is a literature search. The results showed that workload and work stress negatively affect employee job satisfaction.